Association between HALP (hemoglobin, albumin, lymphocyte, and platelet) score and poor outcomes in acute ischemic stroke patients with type 2 diabetes mellitus: a study from the Third China National Stroke Registry - Zhu, Xu; Zhang, Yijun; Wang, Anxin; Zhang, Xiaoli; Yu, Guoyuan; Xiang, Shifeng; Wu, Yiping; Meng, Xia (Frontiers in Neurology, 2025)
BackgroundThe combined index (HALP) of hemoglobin, albumin, lymphocytes, and platelets is considered a novel scoring system that reflects systemic inflammation and nutritional status. This study aimed to investigate the relationship between HALP scores and poor outcomes in acute ischemic stroke (AIS) patients with type 2 diabetes mellitus (DM).MethodsPatients with AIS and type 2 DM were screened from the Third China National Stroke Registry (CNSR-III) and divided into quartiles based on their HALP scores at admission. Clinical outcomes were adverse functional outcomes (modified Rankin scale [mRS] score of 3–6 or 2–6) and all-cause mortality at 3 months and 1 year. The association of HALP with the risk of poor functional outcome and all-cause mortality were analyzed by multivariable logistic regression and Cox proportional hazards regression.ResultsA total of 3,603 patients were included in this study. After adjusting for confounders, it was found that patients in the highest HALP score quartile had lower mRS scores of 2–6 (odds ratio [OR], 0.64; 95% confidence interval [CI], 0.51–0.80) and 3–6 (OR, 0.53; 95% CI, 0.51–0.82) at the 3-month follow-up. At the 1-year follow-up, a significant correlation was observed between HALP scores and mRS scores of 2–6 (OR, 0.65; 95%CI, 0.57–0.81) and 3–6 (OR, 0.64; 95%CI, 0.47–0.86). Additionally, the highest HALP score quartile was associated with a reduced risk of all-cause mortality at the 3-month follow-up (hazard ratio [HR], 0.35; 95%CI, 0.13–0.93). Similar results were observed at the 1-year follow-up (HR, 0.34; 95%CI, 0.18–0.63).ConclusionAt 3 months of AIS patients with type 2 diabetes and 1-year follow-up, lower HALP scores were associated with poorer functional outcomes and all-cause mortality.